Examining the attitude of graduates in relation to the factors hindering employment creation - Taghvaei, Abolghasem (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Unemployment is recognized as a fundamental problem in the society, especially among the graduates of the country's educational system. The aim of this research is to identify the factors preventing graduates from creating employment.Method: This research is applied with a survey-descriptive approach. The statistical population of this research was 180 graduates (both employed and unemployed) of public universities in Tehran, who were selected based on simple random sampling. After collecting the questionnaires, 150 questionnaires were returned. The data collection tool is a researcher-made questionnaire. Data analysis was done using SPSS statistical software.Results: The most important factor preventing employment creation is the lack of government support with a mean of 4.31%. Also, the nature and obstacles of informing are in the next ranks of importance with a mean of 4.07% and 4.03%, respectively.Conclusion: In the present study, which was formed based on the examination of the attitude of the graduates regarding the factors preventing employment in this field, it shows that obstacles such as the lack of government support, the lack of proper training to earn money from professional skills, the nature, information obstacles and individual obstacles and family have a significant role in the lack of employment of graduates of this field. The results of the research show that appropriate training should be provided in the field of acquiring employment skills in order to change the society's view of the nature of the field. Also, the support of the government and more attention of those involved and policy makers will improve the unemployment situation of the graduates of this field.